2017
DOI: 10.1186/s12877-017-0501-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of residential status on cognitive decline among older adults in China: Results from a longitudinal study

Abstract: BackgroundResidential status has been linked to numerous determinants of health and well-being. However, the influence of residential status on cognitive decline remains unclear. The purpose of this research was to assess the changes of cognitive function among older adults with different residential status (urban residents, rural-to-urban residents, rural residents, and urban-to-rural residents), over a 12-year period.MethodsWe used five waves of data (2002, 2005, 2008/2009, 2011/2012, and 2014) from the Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 63 publications
(57 reference statements)
7
39
1
Order By: Relevance
“…However, the differences in cognition were not fully explained by sex and geographic location. Other factors, such as within-country migration, could impact later-life cognitive function [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the differences in cognition were not fully explained by sex and geographic location. Other factors, such as within-country migration, could impact later-life cognitive function [7-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Populationbased studies indicate that cognitive performance in older adults is influenced by sociodemographic characteristics, with level of education, gender, age and income showing consistent associations (Wight et al, 2006). Few studies have also examined the influence of the residential environment (rural or urban) on cognition but the findings have been inconsistent (Crowe et al, 2010;Nunes, et al;Saenz et al, 2018;Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we did not observe a signi cant difference in the rate of cognitive decline between migrants and non-migrants, which might be explained by the following reasons. First, as both rural-to-urban migrants and rural non-migrants had rural life experiences, the differences in the rates of cognitive decline between these populations may be less signi cant than those observed between rural and urban residents [19]. Second, according to Cattell's categorisation of cognitive abilities and previous studies, uid abilities such as memory tend to decline linearly from early adulthood and are more di cult to improve or otherwise change in older adults [30,31,32].…”
Section: Discussionmentioning
confidence: 97%
“…Another study of 1,085 participants in Europe observed poorer cognitive function in non-European migrants than in local citizens [18]. In China, a 12-year longitudinal study indicated that rural-tourban and rural residents exhibited more rapid declines in cognitive function than urban residents [19]. In that study, rural-to-urban migrants were compared with native urban citizens rather than with their rural non-migrant counterparts, although the latter group might be more comparable.…”
Section: Introductionmentioning
confidence: 91%